The Effect of Online Customer Reviews and Ratings on Millennial Purchase Decisions in Banjarbaru through Shopee Marketplace - Mariyani, Kristin; Adista Anjar Diany (LP3M IAI Al-Qolam, 2025)
This study aims to analyze the influence of Online Customer Reviews and Online Customer Ratings on the Purchase Decisions of millennial consumers in Banjarbaru City who shop through the Shopee marketplace. The increasing trend of online shopping among millennials highlights the importance of understanding how consumer-generated information, such as reviews and ratings, shapes trust and affects the decision-making process. This research employs a quantitative approach with 100 respondents who have made purchases on Shopee within the past year. Data were collected using an online questionnaire with a Likert scale and using PLS-SEM to test validity, reliability, and the relationships among variables. The results indicate that both Online Customer Reviews and Online Customer Ratings have a positive and significant influence on Purchase Decisions. These findings suggest that the better and more credible the information shared by other consumers, the stronger the purchase intention among millennials. Practically, this research provides insights for marketers and online sellers to optimize review and rating systems as part of their digital marketing strategies to attract and retain millennial consumers in the competitive marketplace environment.